STATUS HADIS-HADIS YANG DINILAI DA’IF DALAM SAHIH BUKHARI - Mohammad Kurnaini (Al-Majaalis : Jurnal Dirasat Islamiyah, 2022)
A critique of Sahih Bukhari has been from Islamic scholars from time to time. Even if a hadith researcher opens the Sahih Bukhari book and then examines the hadith, sometimes he finds a narrator who is not thiqah in his lineage. This of course raises the question, whether the scholars agree on the validity of all the hadiths contained in the book, or whether there are hadith that are not valid, which Imam Bukhari deliberately included in order to explain its status. Then if it is not valid, can the hadith be used for h}ujjah. In this paper, using a qualitative research approach and the type of library research, we will explain the status of the authenticity of the hadith that were criticized in Sahih Bukhari. The results of this study conclude that there is nothing in Sahih Bukhari’s hadith that cannot be used as hujjah, but there are hadith that are included with the aim of explaining their invalidity.